Pengaruh Kreativitas Pendidik dalam Meningkatkan Minat Belajar Peserta Didik Kelas V pada Pembelajaran Tematik di MIN 2 Makassar - Kartina kartina; Akhmad Syahid; Subaedah Subaedah (Jurnal Ilmiah Islamic Resources, 2023)
Creativity in learning is very important to grow and develop one's potential. Educators have duties and roles as learning resources. One of the factors that influence students' interest in learning is the creativity of educators. This research was conducted to find out 1) how is the creativity of class V educators in thematic learning at MIN 2 Makassar, 2) how is the learning interest of fifth grade students in thematic learning at MIN 2 Makassar, 3) the influence of educator creativity in increasing the learning interest of fifth grade students in learning at MIN 2 Makassar. The type of research used in this research is quantitative using a correlational research approach. This research took place at MIN 2 Makasaar Jl. Freedom Pioneers Km. 15, Daya, Biringkanaya sub-district, Makassar City. This study used a sample of 32 respondents. Data collection techniques were carried out by observation, distributing questionnaires and documentation. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results of this study indicate that the Creativity of Class V Educators in Thematic Learning at MIN 2 Makassar is in the high category with a percentage value of 56.25%. The Learning Interest of Class V Students in Thematic Learning at MIN 2 Makassar is in the high category with a percentage value of 56.25%. The calculation results of the Effect of Educator Creativity in Increasing Learning Interest of Class V Students in Thematic Learning at MIN 2 Makassar using simple linear regression shows a positive effect where the regression equation is Y = 9.225 + 0.910X, this means that if educators' creativity is increased then interest student learning will also increase